Continued Inpatient Care After Elective 1- to 2-level Posterior Lumbar Fusions Increases 30-day Postdischarge Readmissions and Complications. Issue 9 (November 2018) - Malik, Azeem T.; Jain, Nikhil; Kim, Jeffery; Yu, Elizabeth; Khan, Safdar N.
Abstract : Study Design: This was a retrospective cohort study. Objective: The main objective of this article was to investigate the impact of discharge destination on postdischarge outcomes following an elective 1- to 2-level posterior lumbar fusion (PLF) for degenerative pathology. Background Data: Discharge to an inpatient care facility may be associated with adverse outcomes as compared with home discharge. Materials and Methods: The 2012-2016 American College of Surgeons-National Surgical Quality Improvement Program (ACS-NSQIP) database was used to query for patients undergoing PLFs using Current Procedural Terminology (CPT) codes (22612, 22630, and 22633). Additional levels were identified using CPT-22614, CPT-22632, and CPT-22634. Records were filtered to include patients undergoing surgery for degenerative spine pathologies. Only patients undergoing a single-level or 2-level PLF were included in the study. A total of 23, 481 patients were included in the final cohort. Results: A total of 3938 (16.8%) patients were discharged to a skilled care or rehabilitation facility following the primary procedure. Following adjustment for preoperative, intraoperative, and predischarge clinical characteristics, discharge to a skilled care or rehabilitation facility was associated with higher odds of any complication [odds ratio (OR), 1.70; 95% confidence interval (CI), 1.43–2.02], wound complications (OR, 1.73; 95% CI, 1.36–2.20), sepsis-related complications (OR, 1.64; 95% CI, 1.08–2.48), deep venous thrombosis/pulmonary embolism complications (OR, 1.72; 95% CI, 1.10–2.69), urinary tract infections (OR, 1.96; 95% CI, 1.45–2.64), unplanned reoperations (OR, 1.49; 95% CI, 1.23–1.80), and readmissions (OR, 1.29; 95% CI, 1.10–1.49) following discharge. Conclusions: After controlling for predischarge characteristics, discharge to skilled care or rehabilitation facilities versus home following 1- to 2-level PLF is associated with higher odds of complications, reoperations, and readmissions. These results stress the importance of careful patient selection before discharge to inpatient care facilities to minimize the risk of complications. Furthermore, the results further support the need for uniform and standardized care pathways to promote home discharge following hospitalization for elective PLFs. Level of Evidence: Level III.